2017
DOI: 10.1080/0284186x.2016.1275781
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel rectum-prostate spacers mitigate the uncertainties in proton relative biological effectiveness associated with anterior-oblique beams

Abstract: Paganetti (2017) Hydrogel rectum-prostate spacers mitigate the uncertainties in proton relative biological effectiveness associated with anterior-oblique beams, Acta Oncologica, 56:4, 575-581,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…Optimization based upon biologically relevant parameters such as LET d is not yet available in clinical treatment planning systems. Consistent with published studies [25][26][27][28][29][30][31] our findings demonstrated that baseof-skull IMPT plans deemed acceptable under the assumption of a fixed RBE (1.1) did not satisfy OAR constraints when variable RBE modeling was applied. We additionally found the impact of variable RBE modeling to be greater than that of the physical 'worst case' analysis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Optimization based upon biologically relevant parameters such as LET d is not yet available in clinical treatment planning systems. Consistent with published studies [25][26][27][28][29][30][31] our findings demonstrated that baseof-skull IMPT plans deemed acceptable under the assumption of a fixed RBE (1.1) did not satisfy OAR constraints when variable RBE modeling was applied. We additionally found the impact of variable RBE modeling to be greater than that of the physical 'worst case' analysis.…”
Section: Discussionsupporting
confidence: 88%
“…Proton RBE is also known to depend on the intrinsic biological properties of the irradiated cells and the exact biological endpoint considered (e.g., an endpoint of in vitro clonogenic cell survival versus an endpoint of an in-vivo tissue reaction) [24]. Over recent years, there have been a number of published warnings on the possible impact of LET upon clinical treatment plans, including for prostate [25][26][27][28][29][30][31][32], breast [30], thoracic [27,31], liver [32], head and neck [27,31,33], pituitary [27] and various brain tumors [31,32,[34][35][36]. These studies consistently demonstrate that we cannot assume treatment plans to be robust to uncertainties in proton RBE.…”
Section: Introductionmentioning
confidence: 99%
“…Although only considering ±35 proton beams and only using the Wedenberg model, their conclusion was similar to ours as they also were unable to meet the tumor and rectal constraints for both fixed and variable RBE models. Rectal spacers were not included in the patient cohort in our study, but have been shown to be efficient when using AO fields in treatment of prostate cancer [22]. Hence, for the rectum, this could potentially have improved the outcome of our results (e.g., the D 1cm 3 constraint), which proved to be hard to fulfill when evaluated with the variable RBE models.…”
Section: Discussionmentioning
confidence: 99%
“…Four beams were used to generate a more robust plan for stereotactic radiation delivery. The optimal beam arrangement was determined to be opposed lateral and 2 anterior oblique beams, which have been shown to be more robust to modeled RBE elevations when a spaceOAR is in place [ 36 ]. While patients in this study were treated before spaceOAR was routinely used at our institution, it is expected that spaceOAR would be used if this technique is in use clinically.…”
Section: Methodsmentioning
confidence: 99%